2012
DOI: 10.1093/her/cys016
|View full text |Cite
|
Sign up to set email alerts
|

Food sustainability education as a route to healthier eating: evaluation of a multi-component school programme in English primary schools

Abstract: Promising approaches to the promotion of healthier eating among children in primary school settings include the opportunity to practise practical cooking and growing, promoting the take up of healthier school meals and nutritional education. However, less is known about the potential for strategies that integrate approaches through a focus on food sustainability issues--such as the promotion of awareness about local, seasonal, organic, fair trade and higher animal welfare foods. This paper presents an evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 20 publications
2
92
1
1
Order By: Relevance
“…This corresponds with other studies of school-based cooking and gardening projects and effects on children's nutrition (Gibbs et al, 2013;Jones et al, 2012;Passy et al, 2010;Ransley et al, 2010;Wright & Rowell, 2010) and children's food awareness and skills. (Passy et al, 2010;Somerset & Markwell, 2009;Yeatman et al, 2013) This, along with the developing priorities of cooking and nutrition in schools, as evidenced by the revised National Curriculum, is further endorsement of school-based food activities.…”
Section: Discussionsupporting
confidence: 87%
“…This corresponds with other studies of school-based cooking and gardening projects and effects on children's nutrition (Gibbs et al, 2013;Jones et al, 2012;Passy et al, 2010;Ransley et al, 2010;Wright & Rowell, 2010) and children's food awareness and skills. (Passy et al, 2010;Somerset & Markwell, 2009;Yeatman et al, 2013) This, along with the developing priorities of cooking and nutrition in schools, as evidenced by the revised National Curriculum, is further endorsement of school-based food activities.…”
Section: Discussionsupporting
confidence: 87%
“…Awards are categorised at bronze, silver and gold levels to reflect the scope and scale of reforms implemented. Previous research has found that the award levels serve as an indicator of the scale of impact on sustainable food systems [57], for example with respect to greater procurement from local or organic food producers and suppliers [56]. Impacts on the wider consumption behaviours of service users, for example the household food purchases of school parents, is less clearly evidenced although self-report surveys suggest a positive influence [58] FFL presents a valuable case of niche influencing agri-food systems because it is regarded as the "the gold standard" in sustainable school food but had been confined to "islands of good practice" [21], within a public food regime centred on low-cost mass-catering [5].…”
Section: Food For Life Programmementioning
confidence: 99%
“…Although the positive effects of low-energy-dense food have been demonstrated in adults (8) , the data are somewhat inconsistent, particularly among children (9)(10)(11) . While many factors influence dietary preferences and habits, encouraging children to consume recommended amounts of F&V is often part of programming conducted in schools (12)(13)(14)(15)(16)(17)(18) . Schools are common intervention sites for studies in children due to their large, representative populations (19) .…”
Section: Fruits and Vegetables School Lunch Food Wastementioning
confidence: 99%
“…While many factors influence dietary preferences and habits, encouraging children to consume recommended amounts of F&V is often part of programming conducted in schools (12)(13)(14)(15)(16)(17)(18) . Schools are common intervention sites for studies in children due to their large, representative populations (19) .…”
mentioning
confidence: 99%